2017
DOI: 10.1097/ede.0000000000000636
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Burning as a Source of Ambient Fine Particulate Air Pollution and Acute Myocardial Infarction

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 30 publications
2
44
0
2
Order By: Relevance
“…Weichenthal et al ( 2017 ) reported a significant 6% increase in the odds of MI hospital admissions associated with increased concentrations of PM 2.5 in the previous 3 days among elderly subjects (≥ 65 years of age), but not young subjects (< 65), among residents of three regions of British Columbia, Canada. Further, the strongest associations were observed in the cold season when monthly mean biomass burning contributions to PM 2.5 (based on ambient levoglucosan/PM 2.5 ) were in the highest tertile (OR = 1.19; 95% CI = 1.04, 1.36).…”
Section: Discussionmentioning
confidence: 99%
“…Weichenthal et al ( 2017 ) reported a significant 6% increase in the odds of MI hospital admissions associated with increased concentrations of PM 2.5 in the previous 3 days among elderly subjects (≥ 65 years of age), but not young subjects (< 65), among residents of three regions of British Columbia, Canada. Further, the strongest associations were observed in the cold season when monthly mean biomass burning contributions to PM 2.5 (based on ambient levoglucosan/PM 2.5 ) were in the highest tertile (OR = 1.19; 95% CI = 1.04, 1.36).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a 2015 emissions inventory for the Comox Valley airshed indicated that 35% of all fine particulate matter (PM 2.5 ) was from residential wood burning [29]. Concurrent ambient air quality studies used levoglucosan [30] concentrations to confirm that woodsmoke is a major contributor to the total PM 2.5 in this region [31,32]. It is important to note that the topography and climate of Vancouver Island favor the pooling of smoke in valleys and along the coast, particularly under inversion conditions.…”
Section: Vancouver Island-reliance On Mechanical Thinning and Pile Bumentioning
confidence: 99%
“…Epidemiological studies have reported that ambient air pollution are associated with poor health outcomes, including respiratory diseases [3,4], cardiovascular diseases [5,6], and mortality [7,8]. In addition, exposure to air pollution is associated with airway in ammation and impairs lung function [9,10].…”
Section: Introductionmentioning
confidence: 99%